TEACHERSÃ¢â¬â¢ PROFESSIONAL DEVELOPMENT THROUGH AN OBSERVATION IN IMMERSION CLASSES BASED ON THE DOCUMENTS AND TEACHING AND LEARNING PROCESSES - Bharati, Dwi Anggani Linggar (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2010)
Immersion program, the learning and teaching process conducted in English, has become a new trend in Indonesia nowadays in which almost every school is trying to conduct it. However, not many of the schools can do that program for it requires professional teachers, not only being able to teach in English well but also able toÃÂ prepareÃÂ the documents, making lesson plan, syllabus and media,ÃÂ needed for the program. Professional teachers are badly required for the immersion classes for they play an important role in succeeding the program. Therefore, it is worth investigating to see whether the real condition of the teachers is as it is expected or not and finally, conclusions and suggestions can be put forward for the betterment of the program. Based on the observation done by the writer, it was found out that mispronunciation, misspelled, grammar mistakes, wrong diction, and some other linguistic feature problems often happened in the classroom activities. Besides, other problems were also found in the development of teaching documents, syllabus, lesson plan, and media. The development of those documents was not in line with the school- based curriculum, ignoring the level of difficulty as stated in the Bloom Taxonomy revised by Anderson. The objectives, the indicators, the evaluation formulations were still on surface and incomplete. In this paper the writer tries to show the complete result of her observation dealing with the real condition of the teachersÃ¢â¬â¢ competence in their teaching and learning process in English as well as their competence in developing the documents and finally give some suggestions for increasing their competence, especially in preparing their teaching documents. ÃÂ Key Words: immersion class teacher, professionalism, teaching documents, teachingÃÂ ÃÂ and learning process